Effect of Dietary Zinc Supplementation on Some Seminal Plasma Characteristics of Broiler Breeders' Males - Amen, Mahmood H.M.; Al-Daraji , Hazim J. (International Journal of Poultry Science, 2011)
The aim of the present study was to evaluate the effect of zinc (Zn) as feed additive on certain seminal plasma traits of broiler breeders' males. A total of 36 Cobb 500 broiler breeders males, 45 weeks old were used in this study. These birds were randomly distributed equally into four dietary treatments with three replicates each. Each treatment group constituted 9 males. Treatment groups were as following: T1: Birds fed the basal diet without any addition of zinc (0 Zn) (control), T2: Birds fed diet supplemented with 50 mg Zn (pure zinc)/kg of diet, T3: Birds fed diet supplemented with 75 mg Zn (pure zinc)/kg of diet and T4: Birds fed diet supplemented with 100 mg Zn (pure zinc)/kg of diet. Results revealed that adding zinc to the diet of roosters (T2, T3 and T4) resulted in significant (p